Gastric Fluid Volume in Patients Fasting for Clear Fluid Ingestion from Midnight Versus 2 Hours Prior Laparoscopic Cholecystectomy - Anil Kumar, Syed Farjad Sultan, Mehar Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the mean gastric fluid volume in the group ingesting clear fluid 8 hours prior to surgery (8-hour group) in comparison to the group ingesting clear liquid 2 hours prior to surgery (2-hour group) Study Design: Randomized controlled trial Place and Duration of Study: Department of Anesthesiology, The Indus Hospital, Karachi from 30th June 2016to 20th May 2017. Methodology: Sixty eligible patients were identified in the preoperative visit and all study detail was discussed with the patients and informed consent was obtained. Patients were divided two equal groups through randomization i.e. 2 hours fasting prior to surgery versus 8 hours fasting prior to surgery. The insertion of nasogastric tube is required in all laparoscopic cholecystectomies to deflate the stomach, not only to improve surgical view but also to avoid gastric injury on trocar insertion. Aspirate from stomach was through 20ml syringe. Volume of aspirate was also noted. Results: Mean age in 2 hours fasting prior to surgery and 8 hours fasting prior to surgery was 36.20±10.14 with CI (32.41-39.98) and 38.90±10.27 with C.I (35.06-42.73) years respectively. Five (16.7%) male and 25 (83.3%) female was enrolled in 2 hours fasting prior to surgery group and 6 (20.0%) male and 24 (80.0%) female were included in 8 hours fasting prior to surgery group. In comparison of both groups, mean of 2 hours prior to surgery group was 11.53±3.68 and in 8 hours prior to surgery group was 13.66±5.32 and P value found to be non-significant (p=0.076). Conclusion: There was no significant difference in mean gastric fluid volume between the group ingesting clear fluid 8 hours prior to surgery (8-hour group) in comparison to the group ingesting clear liquid 2 hours prior to surgery (2-hour group).